Optimizing Time of Initiation for Triploid Walleye Production Using Pressure Shock Treatment. (28th August 2015) - Fetherman, Eric R.; Lepak, Jesse M.; Brown, Bonnie L.; Harris, David J.
Abstract: Walleyes Sander vitreus support important recreational and commercial fisheries, and have been introduced into many systems throughout the United States and Canada. Use of sterile triploid fish is a valuable management strategy for protecting native fish species from naturally reproducing populations of introduced predators like Walleyes. Hydrostatic pressure is one of the more effective methods for inducing triploidy in Walleyes, and the technique is currently evolving. A 2.7‐L capacity electric pressure chamber (TRC‐APV Aqua Pressure Vessel; TRC Hydraulics) was used to produce triploid Walleyes using hydrostatic pressure with eggs collected from Pueblo Reservoir, Colorado. The TRC‐APV has many advantages over manually operated pressure chambers including its portability, large capacity, and safety. Here, the methods used to create triploid Walleyes using the TRC‐APV and the flow cytometric methods for estimating the efficacy of ploidy induction from pooled samples of fry are described. In addition, times of initiation (TIs), the times between fertilization and when eggs were subjected to pressure, were varied to determine the optimal time for maximizing induction and hatching success rates. Results suggest that triploidy in Walleyes is maximized with a TI of approximately 7.5 min, whereas hatching success is maximized with a TI of just over 8 min.